Imagining Sanctuary: Politics of Storytelling, Care, and Refusal at Farm Animal Sanctuaries - Salazar, Ana (Tufts Archival Research Center, 2022)
In working through the paradoxes and tensions that exist at farm sanctuaries, this thesis demonstrates that sanctuaries can help us see the potential of creating new stories about how we live and work alongside nonhuman animals, as an intervention into an under-questioned world underpinned by exploitation and killability. The stories that emerge from the events at sanctuaries allow us to see what day-to-day lives and relationships can be when we refuse systems of capitalist production and industrial animal agriculture. Sanctuaries’ existence right now as spaces of transition and temporary oasis is crucial, as are the stories and acts of care within them, because they prove that different ways of living are not simply aspirational but entirely possible.; Thesis (B.A.)--Tufts University, 2022.; Submitted to the Dept. of Anthropology.